Arduino by Example - Adith Jagadish Boloor (Birmingham : Packt Publishing Ltd, 2015)
Arduino an opensource physical computing platform based on a simple microcontroller board, and a development environment for writing software for the board. The opensource Arduino software (IDE) makes it easy to write code and upload it to the board. It runs on Windows, Mac OS X, and Linux. The environment is written in Java and based on Processing and other opensource software.
Includes index.
Keywords: Arduino by Example